Partnership of contract farming system is the one of solution for economic problem in Indonesia. PT Aqua Farm Nusantara has been carried out contract farming system with small fish farmers in Kalasan Sub-district, Sleman Regency, Special Region of Yogyakarta Province.The research uses a case study method, and purposive sampling is made to get primary and secondary data. The research is aimed to learn contract-farming implementation technically, to identify obstacles and benefit of contract farmi - Bayu Cahyono; Dinarwan .; Narni Farmayanti (Buletin Ekonomi Perikanan, 2007)
Partnership of contract farming system is the one of solution for economic problem in Indonesia. PT Aqua Farm Nusantara has been carried out contract farming system with small fish farmers in Kalasan Sub-district, Sleman Regency, Special Region of Yogyakarta Province.The research uses a case study method, and purposive sampling is made to get primary and secondary data. The research is aimed to learn contract-farming implementation technically, to identify obstacles and benefit of contract farming system, and to analyze impact of the system between the company and its partner and non-partner fish farmers. Qualitative and quantitative data method is used to calculate the outcome of the farms of the participants. Mann-Whitney Test has been used to observe real respective income of partner and non-partner fish farmers. The result of study shows that based on cash and total cost calculation, incomes of nonpartner are bigger than partner fish farmers'. The R-C Ratio Analysis based on the cash cost of the farming indicates that the partner and the non-partner fish farmers still gain profit. R-C Ratios of both participants are higher than 1 point. The result of the analysis and calculation indicate that contract farming system is still able to be sustained, because the partner fish farmers can cover the cost, and get profit from their farm in an outline of contract farming system.